Strategi Efektif Pengendalian Persediaan Barang Jadi Dalam Bisnis Mochi AO Daifuku: Meningkatkan Efisiensi dan Kelayakan Operasional - Yunita, Anggita Vira; Putri, Arfie Laillya Azrawanda; Sulistyowati, Yana (PUTRA JAWA PUBLISHER, 2024)
The development of the food business is currently experiencing quite rapid growth. The reason is that more and more new foods are emerging and innovating. One of them is the sweet mochi food business